2021
DOI: 10.1161/hypertensionaha.121.17622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Experimental Sleep Restriction on Ambulatory and Sleep Blood Pressure in Healthy Young Adults: A Randomized Crossover Study

Abstract: Although insufficient sleep is associated with increased cardiovascular risk, evidence of a causal relationship is lacking. We investigated the effects of prolonged sleep restriction on 24-hour ambulatory blood pressure (BP) and other cardiovascular measures in 20 healthy young participants (aged 23.4±4.8 years, 9 females), who underwent a randomized, controlled, crossover, 16-day inpatient study consisting of 4 days of acclimation, 9 days of sleep restriction (4 hours of sleep/night) or control sleep (9 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 61 publications
0
28
0
4
Order By: Relevance
“…Furthermore, Sweeney et al (56) assessed glucose tolerance after each night of sleep restriction (4 h TIB for 4 nights) and observed that although glucose tolerance was reduced with SR, this impairment did not occur in a cumulative manner. Similarly, sleep-loss-induced changes in blood pressure and endothelial function are highest after one night of sleep (4 h TIB) and gradually decrease over multiple nights (57), and increased energy intake is reported in the early phases of sleep restriction protocols before returning to baseline levels on subsequent nights (58,59). These findings suggest an adaptive physiological response to the stress of sleep restriction that occurs over extended periods; this same phenomenon may help to explain the results in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Sweeney et al (56) assessed glucose tolerance after each night of sleep restriction (4 h TIB for 4 nights) and observed that although glucose tolerance was reduced with SR, this impairment did not occur in a cumulative manner. Similarly, sleep-loss-induced changes in blood pressure and endothelial function are highest after one night of sleep (4 h TIB) and gradually decrease over multiple nights (57), and increased energy intake is reported in the early phases of sleep restriction protocols before returning to baseline levels on subsequent nights (58,59). These findings suggest an adaptive physiological response to the stress of sleep restriction that occurs over extended periods; this same phenomenon may help to explain the results in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial function was impaired and plasma norepinephrine increased during the phase of sleep restriction. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Endothelial function was impaired and plasma norepinephrine increased during the phase of sleep restriction. 27 Environmental factors including seasonality and atmospheric conditions also have impact on the diurnal BP profile. 17,18,28 In a metaanalysis involving 856 539 participants in 47 studies, 28 office, daytime and home BPs, but not nighttime BP, were significantly lower in summer than in winter.…”
Section: Clock Genes In Relation To Inhmentioning
confidence: 99%
“…Experimental sleep deprivation and sleep restriction paradigms have reported elevated levels of sympathetic activity following acute sleep impairment. [7][8][9] Dysfunction of the sympathetic nervous system is similarly observed within sleep disorders, 10,11 as well as cardiometabolic disorders such as hypertension and 12 heart failure. 13 Despite these findings, the central regulatory mechanisms underpinning these associations has not been established in humans.…”
mentioning
confidence: 99%